The Use of Effective Questioning Types on Students Critical Reading Skills - Ayra Zalikha Munir; Munir Munir; Chairil Anwar Korompot (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
This research aimed to investigate the use of effective questioning types on students’ critical reading skills. Motivated by the lack of student engagement in reading tasks and the difficulty students face in higher-order comprehension, this study implemented a framework of structured questions—analytical, evaluative, interpretive, inferential, and synthetic—to enhance critical reading. A pre-experimental design was employed using a one-group pre-test and post-test format. Thirty-two tenth-grade students from SMK Negeri 10 Makassar participated in the study. The findings showed a statistically significant improvement in students’ performance following the treatment. The mean score increased from 57.06 in the pre-test to 64.22 in the post-test. Score distribution also shifted notably, with 41% of students reaching the “Very Good” category and only 9% remaining in the “Requiring Guidance” classification, compared to 66% before the treatment. The Wilcoxon Signed-Rank Test yielded a Z-value of -4.795 and a significance level of p < .001, confirming that the improvement was not due to chance. These findings suggest that effective questioning types promoted students’ higher-order thinking and engagement with texts. This study contributes to the growing body of research on reading pedagogy by addressing the gap in literature concerning the use of targeted questioning types in critical reading instruction. Future research may explore the comparative effectiveness of each questioning type and incorporate qualitative data to gain deeper insights into student responses. The implications of this study suggest that structured questioning can be a powerful tool in helping students think more deeply and critically. It shows that when students are guided with the right types of questions, they are more likely to reflect, analyze, and make meaningful connections with the texts they read. This approach could help improve the way reading is taught, especially in EFL classrooms, by encouraging more active and thoughtful learning.Keywords: effective questioning types, critical reading, higher-order thinking, EFL, reading comprehension